The influence of job analysis and Job enlargement on employee performance with work engagement as an intervening variable among Generation Z working in the Financial Services Industry in Surabaya. - Elizabeth Linggawati; Meirani Harsasi; Anita Maharani (Priviet Social Sciences Journal, 2023)
This study focuses on discussing the influence of job analysis and job enlargement on employee performance, as well as the influence of work engagement as an intermediary variable between job analysis, job enlargement, and employee performance among Generation Z employees working in the financial services industry in Surabaya. Data collection was conducted using online questionnaires, from which 164 respondents were eventually gathered. The collected data was analyzed using the PLS-SEM approach and using Smart PLS 4 software. From the analysis, it was found that job analysis has a positive but not significant effect on employee performance, job enlargement has no effect on employee performance, there is no influence whatsoever of work engagement between job analysis and employee performance, and there is no influence whatsoever of work engagement between job enlargement and employee performance.